Resources for the practice of pediatric neuro-oncology in Mexico: a cross-sectional evaluation - Arce-Cabrera, Daniela; Escamilla-Asiain, Gabriela; Nájera-Castillo, Melisa F.; Navarro-Martín del Campo, Regina M.; Ortiz-Azpilcueta, Mariana; Pantoja-Guillén, Francisco J.; Arreguín González, Farina E.; Zapata-Sosa, Imelda; Lugo-Juárez, Jocelyn Z.; Santillán Cortéz, Daniel; Morales-La Madrid, Andrés; Moreira, Daniel C.; et al. (Frontiers in Oncology, 2024)
Background: The evaluation of existing resources and services is key to identify gaps and prioritize interventions to expand care capacity for children with central nervous system (CNS) tumors. We sought to evaluate the resources for pediatric neuro-oncology (PNO) in Mexico. Methods: A cross-sectional online survey with 35 questions was designed to assess PNO resources and services, covering aspects including number of patients, infrastructure, human resources, and diagnostic and treatment time intervals. The survey was distributed to the members of the Mexican Association of Pediatric Oncology and Hematology (AMOHP) who belong to the nation’s many different health systems. Results: Responses were obtained from 33 institutions, distributed throughout the country and part of the many health systems that exist in Mexico. Twenty-one (64%) institutions had less than 10 new cases of pediatric CNS tumors per year. Although 30 (91%) institutions saw pediatric patients up to the age of 18 years, 2 (6%) had a cutoff of 15 years. Twenty-four (73%) institutions had between 1 and 3 pediatric oncologists providing care for children with CNS tumors. Six (18%) institutions did not have a neurosurgeon, while 19 (57%) institutions had a pediatric neurosurgeon. All centers had a pathology department, but 13 (39%) institutions only had access to basic histopathology. Eleven (33%) institutions reported histopathological diagnoses within one week, but 3 (9%) took more than 4 weeks. Radiotherapy for pediatric CNS tumors was referred to outside centers at 18 (55%) institutions. All centers had access to conventional cytotoxic chemotherapy, but only 6 (18%) had access to targeted therapy. Eighteen (55%) respondents estimated a survival rate of less than 60%. Fifteen (45%) centers attributed the main cause of mortality to non-tumor related factors, including infection and post-surgical complications. Conclusions: This is the first national assessment of the resources available in Mexico for the treatment of CNS tumors. It shows disparities in resource capacity and a lack of the specific and efficient diagnoses that allow timely initiation of treatment. These data will enable the prioritization of collaborative interventions in the future.